Non relativistic quantum field theory: Dynamics and irreversibility - Daguerre, L.; Torroba, G.; Medina Ramos, Raimel A; Solís, M. (Anales de la Asociacion Fisica Argentina)
studiamos aspectos de Teoría Cuántica de Campos a densidad finita usando técnicas y conceptos de información cuántica. Nos enfocamos en fermiones de Dirac masivos con potencial químico en 1+1 dimensiones espacio-temporales. Usando la entropía de entrelazamiento en un intervalo, construimos la función c entrópica que es finita. Esta función c no es monótona, e incorpora el entrelazamiento de largo alcance proveniente de la superficie de Fermi. Motivados por trabajos previos de modelos en la red, calculamos numéricamente las entropías de Renyi y encontramos oscilaciones de Friedel. Seguidamente, analizamos la información mutua como una medida de correlación entre diferentes regiones. Usando una expansión de distancia grande desarrollada por Cardy, argumentamos que la información mutua detecta las correlaciones inducidas por la superficie de Fermi todavía al orden dominante en la expansión. Finalmente, analizamos la entropía relativa y sus generalizaciones de Renyi para distinguir estados con diferente carga. Encontramos que estados en diferentes sectores de superselección dan origen a un comportamiento super-extensivo en la entropía relativa.

Theory of chirality induced spin selectivity: Progress and challenges - Evers, Ferdinand; Aharony, Amnon; Bar-Gill, Nir; Entin-Wohlman, Ora; Hedegård, Per; Hod, Oded; Jelinek, Pavel; Kamieniarz, Grzegorz; Lemeshko, Mikhail; Michaeli, Karen; Mujica, Vladimiro; Naaman, Ron; et al. (Advanced Materials)
A critical overview of the theory of the chirality-induced spin selectivity (CISS) effect, that is, phenomena in which the chirality of molecular species imparts significant spin selectivity to various electron processes, is provided. Based on discussions in a recently held workshop, and further work published since, the status of CISS effects—in electron transmission, electron transport, and chemical reactions—is reviewed. For each, a detailed discussion of the state-of-the-art in theoretical understanding is provided and remaining challenges and research opportunities are identified.

Mirror symmetry for the Tate curve via tropical and log corals - Arguez, Nuroemuer Huelya (Journal of the London Mathematical Society)
We introduce tropical corals, balanced trees in a half-space, and show that they correspond to holomorphic polygons capturing the product rule in Lagrangian Floer theory for the elliptic curve. We then prove a correspondence theorem equating counts of tropical corals to punctured log Gromov–Witten invariants of the Tate curve. This implies that the homogeneous coordinate ring of the mirror to the Tate curve is isomorphic to the degree-zero part of symplectic cohomology, confirming a prediction of homological mirror symmetry.

Continuous and discrete radius functions on Voronoi tessellations and Delaunay mosaics - Biswas, Ranita; Cultrera Di Montesano, Sebastiano; Edelsbrunner, Herbert; Saghafian, Morteza (Discrete and Computational Geometry)
The Voronoi tessellation in Rd is defined by locally minimizing the power distance to given weighted points. Symmetrically, the Delaunay mosaic can be defined by locally maximizing the negative power distance to other such points. We prove that the average of the two piecewise quadratic functions is piecewise linear, and that all three functions have the same critical points and values. Discretizing the two piecewise quadratic functions, we get the alpha shapes as sublevel sets of the discrete function on the Delaunay mosaic, and analogous shapes as superlevel sets of the discrete function on the Voronoi tessellation. For the same non-critical value, the corresponding shapes are disjoint, separated by a narrow channel that contains no critical points but the entire level set of the piecewise linear function.

Flavors of sequential information flow - Bartocci, Ezio; Ferrere, Thomas; Henzinger, Thomas A; Nickovic, Dejan; Da Costa, Ana Oliveira (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics))
We study the problem of specifying sequential information-flow properties of systems. Information-flow properties are hyperproperties, as they compare different traces of a system. Sequential information-flow properties can express changes, over time, in the information-flow constraints. For example, information-flow constraints during an initialization phase of a system may be different from information-flow constraints that are required during the operation phase. We formalize several variants of interpreting sequential information-flow constraints, which arise from different assumptions about what can be observed of the system. For this purpose, we introduce a first-order logic, called Hypertrace Logic, with both trace and time quantifiers for specifying linear-time hyperproperties. We prove that HyperLTL, which corresponds to a fragment of Hypertrace Logic with restricted quantifier prefixes, cannot specify the majority of the studied variants of sequential information flow, including all variants in which the transition between sequential phases (such as initialization and operation) happens asynchronously. Our results rely on new equivalences between sets of traces that cannot be distinguished by certain classes of formulas from Hypertrace Logic. This presents a new approach to proving inexpressiveness results for HyperLTL.

List-decodability with large radius for Reed-Solomon codes - Ferber, Asaf; Kwan, Matthew Alan; Sauermann, Lisa (IEEE Transactions on Information Theory)
List-decodability of Reed–Solomon codes has received a lot of attention, but the best-possible dependence between the parameters is still not well-understood. In this work, we focus on the case where the list-decoding radius is of the form r = 1-ε for ε tending to zero. Our main result states that there exist Reed–Solomon codes with rate Ω(ε) which are (1 - ε, O(1/ε))-list-decodable, meaning that any Hamming ball of radius 1-ε contains at most O(1/ε) codewords. This trade-off between rate and list-decoding radius is best-possible for any code with list size less than exponential in the block length. By achieving this trade-off between rate and list-decoding radius we improve a recent result of Guo, Li, Shangguan, Tamo, and Wootters, and resolve the main motivating question of their work. Moreover, while their result requires the field to be exponentially large in the block length, we only need the field size to be polynomially large (and in fact, almost-linear suffices). We deduce our main result from a more general theorem, in which we prove good list-decodability properties of random puncturings of any given code with very large distance.

Barycentric cuts through a convex body - Patakova, Zuzana; Tancer, Martin; Wagner, Uli (Discrete and Computational Geometry)
Let K be a convex body in Rn (i.e., a compact convex set with nonempty interior). Given a point p in the interior of K, a hyperplane h passing through p is called barycentric if p is the barycenter of K∩h. In 1961, Grünbaum raised the question whether, for every K, there exists an interior point p through which there are at least n+1 distinct barycentric hyperplanes. Two years later, this was seemingly resolved affirmatively by showing that this is the case if p=p0 is the point of maximal depth in K. However, while working on a related question, we noticed that one of the auxiliary claims in the proof is incorrect. Here, we provide a counterexample; this re-opens Grünbaum’s question. It follows from known results that for n≥2, there are always at least three distinct barycentric cuts through the point p0∈K of maximal depth. Using tools related to Morse theory we are able to improve this bound: four distinct barycentric cuts through p0 are guaranteed if n≥3.

The response of a metapopulation to a changing environment - Barton, Nicholas H; Olusanya, Oluwafunmilola O (Philosophical Transactions of the Royal Society B: Biological Sciences)
A species distributed across diverse environments may adapt to local conditions. We ask how quickly such a species changes its range in response to changed conditions. Szép et al. (Szép E, Sachdeva H, Barton NH. 2021 Polygenic local adaptation in metapopulations: a stochastic eco-evolutionary model. Evolution75, 1030–1045 (doi:10.1111/evo.14210)) used the infinite island model to find the stationary distribution of allele frequencies and deme sizes. We extend this to find how a metapopulation responds to changes in carrying capacity, selection strength, or migration rate when deme sizes are fixed. We further develop a ‘fixed-state’ approximation. Under this approximation, polymorphism is only possible for a narrow range of habitat proportions when selection is weak compared to drift, but for a much wider range otherwise. When rates of selection or migration relative to drift change in a single deme of the metapopulation, the population takes a time of order m−1 to reach the new equilibrium. However, even with many loci, there can be substantial fluctuations in net adaptation, because at each locus, alleles randomly get lost or fixed. Thus, in a finite metapopulation, variation may gradually be lost by chance, even if it would persist in an infinite metapopulation. When conditions change across the whole metapopulation, there can be rapid change, which is predicted well by the fixed-state approximation. This work helps towards an understanding of how metapopulations extend their range across diverse environments. This article is part of the theme issue ‘Species’ ranges in the face of changing environments (Part II)’.
Keywords: General Agricultural and Biological Sciences; General Biochemistry; Genetics and Molecular Biology

Integral points of bounded height on a certain toric variety - Wilsch, Florian Alexander (arXiv)
We determine an asymptotic formula for the number of integral points of bounded height on a certain toric variety, which is incompatible with part of a preprint by Chambert-Loir and Tschinkel. We provide an alternative interpretation of the asymptotic formula we get. To do so, we construct an analogue of Peyre's constant $α$ and describe its relation to a new obstruction to the Zariski density of integral points in certain regions of varieties.
Keywords: Integral point; toric variety; Manin's conjecture

Tissue-wide effects override cell-intrinsic gene function in radial neuron migration - Hansen, Andi H; Pauler, Florian; Riedl, Michael; Streicher, Carmen; Heger, Anna-Magdalena; Laukoter, Susanne; Sommer, Christoph M; Nicolas, Armel; Hof, Björn; Tsai, Li Huei; Rülicke, Thomas; Hippenmeyer, Simon (Oxford Open Neuroscience)
The mammalian neocortex is composed of diverse neuronal and glial cell classes that broadly arrange in six distinct laminae. Cortical layers emerge during development and defects in the developmental programs that orchestrate cortical lamination are associated with neurodevelopmental diseases. The developmental principle of cortical layer formation depends on concerted radial projection neuron migration, from their birthplace to their final target position. Radial migration occurs in defined sequential steps, regulated by a large array of signaling pathways. However, based on genetic loss-of-function experiments, most studies have thus far focused on the role of cell-autonomous gene function. Yet, cortical neuron migration in situ is a complex process and migrating neurons traverse along diverse cellular compartments and environments. The role of tissue-wide properties and genetic state in radial neuron migration is however not clear. Here we utilized mosaic analysis with double markers (MADM) technology to either sparsely or globally delete gene function, followed by quantitative single-cell phenotyping. The MADM-based gene ablation paradigms in combination with computational modeling demonstrated that global tissue-wide effects predominate cell-autonomous gene function albeit in a gene-specific manner. Our results thus suggest that the genetic landscape in a tissue critically affects the overall migration phenotype of individual cortical projection neurons. In a broader context, our findings imply that global tissue-wide effects represent an essential component of the underlying etiology associated with focal malformations of cortical development in particular, and neurological diseases in general.

WDFY3 cell autonomously controls neuronal migration - Schaaf, Zachary; Tat, Lyvin; Cannizzaro, Noemi; Green, Ralph; Rülicke, Thomas; Hippenmeyer, Simon; Zarbalis, K
Background Proper cerebral cortical development depends on the tightly orchestrated migration of newly born neurons from the inner ventricular and subventricular zones to the outer cortical plate. Any disturbance in this process during prenatal stages may lead to neuronal migration disorders (NMDs), which can vary in extent from focal to global. Furthermore, NMDs show a substantial comorbidity with other neurodevelopmental disorders, notably autism spectrum disorders (ASDs). Our previous work demonstrated focal neuronal migration defects in mice carrying loss-of-function alleles of the recognized autism risk gene WDFY3. However, the cellular origins of these defects in Wdfy3 mutant mice remain elusive and uncovering it will provide critical insight into WDFY3-dependent disease pathology . Methods Here, in an effort to untangle the origins of NMDs in Wdfy3lacZ mice, we employed mosaic analysis with double markers (MADM). MADM technology enabled us to genetically distinctly track and phenotypically analyze mutant and wild type cells concomitantly in vivo using immunofluorescent techniques. Results We revealed a cell autonomous requirement of WDFY3 for accurate laminar positioning of cortical projection neurons and elimination of mispositioned cells during early postnatal life. In addition, we identified significant deviations in dendritic arborization, as well as synaptic density and morphology between wild type, heterozygous, and homozygous Wdfy3 mutant neurons in Wdfy3-MADM reporter mice at postnatal stages. Limitations While Wdfy3 mutant mice have provided valuable insight into prenatal aspects of ASD pathology that remain inaccessible to investigation in humans, like most animal models, they do not a perfectly replicate all aspects of human ASD biology. The lack of human data makes it indeterminate whether morphological deviations described here apply to ASD patients. Conclusions ﻿Our genetic approach revealed several cell autonomous requirements of Wdfy3 in neuronal development that could underly the pathogenic mechanisms of WDFY3-related ASD conditions. The results are also consistent with findings in other ASD animal models and patients and suggest an important role for Wdfy3 in regulating neuronal function and interconnectivity in postnatal life.

Orthogonal polynomial duality of boundary driven particle systems and non-equilibrium correlations - Floreani, Simone; Redig, Frank; Sau, Federico (Annales de l'institut Henri Poincare (B) Probability and Statistics)
We consider symmetric partial exclusion and inclusion processes in a general graph in contact with reservoirs, where we allow both for edge disorder and well-chosen site disorder. We extend the classical dualities to this context and then we derive new orthogonal polynomial dualities. From the classical dualities, we derive the uniqueness of the non-equilibrium steady state and obtain correlation inequalities. Starting from the orthogonal polynomial dualities, we show universal properties of n-point correlation functions in the non-equilibrium steady state for systems with at most two different reservoir parameters, such as a chain with reservoirs at left and right ends.

Robustness and fairness in machine learning - Konstantinov, Nikola H
Because of the increasing popularity of machine learning methods, it is becoming important to understand the impact of learned components on automated decision-making systems and to guarantee that their consequences are beneficial to society. In other words, it is necessary to ensure that machine learning is sufficiently trustworthy to be used in real-world applications. This thesis studies two properties of machine learning models that are highly desirable for the sake of reliability: robustness and fairness. In the first part of the thesis we study the robustness of learning algorithms to training data corruption. Previous work has shown that machine learning models are vulnerable to a range of training set issues, varying from label noise through systematic biases to worst-case data manipulations. This is an especially relevant problem from a present perspective, since modern machine learning methods are particularly data hungry and therefore practitioners often have to rely on data collected from various external sources, e.g. from the Internet, from app users or via crowdsourcing. Naturally, such sources vary greatly in the quality and reliability of the data they provide. With these considerations in mind, we study the problem of designing machine learning algorithms that are robust to corruptions in data coming from multiple sources. We show that, in contrast to the case of a single dataset with outliers, successful learning within this model is possible both theoretically and practically, even under worst-case data corruptions. The second part of this thesis deals with fairness-aware machine learning. There are multiple areas where machine learning models have shown promising results, but where careful considerations are required, in order to avoid discrimanative decisions taken by such learned components. Ensuring fairness can be particularly challenging, because real-world training datasets are expected to contain various forms of historical bias that may affect the learning process. In this thesis we show that data corruption can indeed render the problem of achieving fairness impossible, by tightly characterizing the theoretical limits of fair learning under worst-case data manipulations. However, assuming access to clean data, we also show how fairness-aware learning can be made practical in contexts beyond binary classification, in particular in the challenging learning to rank setting.
Keywords: robustness; fairness; machine learning; PAC learning; adversarial learning

Fairness-aware PAC learning from corrupted data - Konstantinov, Nikola H; Lampert, Christoph (Journal of Machine Learning Research)
Addressing fairness concerns about machine learning models is a crucial step towards their long-term adoption in real-world automated systems. While many approaches have been developed for training fair models from data, little is known about the robustness of these methods to data corruption. In this work we consider fairness-aware learning under worst-case data manipulations. We show that an adversary can in some situations force any learner to return an overly biased classifier, regardless of the sample size and with or without degrading accuracy, and that the strength of the excess bias increases for learning problems with underrepresented protected groups in the data. We also prove that our hardness results are tight up to constant factors. To this end, we study two natural learning algorithms that optimize for both accuracy and fairness and show that these algorithms enjoy guarantees that are order-optimal in terms of the corruption ratio and the protected groups frequencies in the large data limit.
Keywords: Fairness; robustness; data poisoning; trustworthy machine learning; PAC learning

The physiology and genetics of bacterial responses to antibiotic combinations - Römhild, Roderich; Bollenbach, Mark Tobias; Andersson, Dan I. (Nature Reviews Microbiology)
Several promising strategies based on combining or cycling different antibiotics have been proposed to increase efficacy and counteract resistance evolution, but we still lack a deep understanding of the physiological responses and genetic mechanisms that underlie antibiotic interactions and the clinical applicability of these strategies. In antibiotic-exposed bacteria, the combined effects of physiological stress responses and emerging resistance mutations (occurring at different time scales) generate complex and often unpredictable dynamics. In this Review, we present our current understanding of bacterial cell physiology and genetics of responses to antibiotics. We emphasize recently discovered mechanisms of synergistic and antagonistic drug interactions, hysteresis in temporal interactions between antibiotics that arise from microbial physiology and interactions between antibiotics and resistance mutations that can cause collateral sensitivity or cross-resistance. We discuss possible connections between the different phenomena and indicate relevant research directions. A better and more unified understanding of drug and genetic interactions is likely to advance antibiotic therapy.
Keywords: General Immunology and Microbiology; Microbiology; Infectious Diseases

Threshold potentials for fast kinetics during mediated redox catalysis of insulators in Li–O2 and Li–S batteries - Cao, Deqing; Shen, Xiaoxiao; Wang, Aiping; Yu, Fengjiao; Wu, Yuping; Shi, Siqi; Freunberger, Stefan Alexander; Chen, Yuhui (Nature Catalysis)
Redox mediators could catalyse otherwise slow and energy-inefficient cycling of Li–S and Li–O2 batteries by shuttling electrons or holes between the electrode and the solid insulating storage materials. For mediators to work efficiently they need to oxidize the solid with fast kinetics but with the lowest possible overpotential. However, the dependence of kinetics and overpotential is unclear, which hinders informed improvement. Here, we find that when the redox potentials of mediators are tuned via, for example, Li+ concentration in the electrolyte, they exhibit distinct threshold potentials, where the kinetics accelerate several-fold within a range as small as 10 mV. This phenomenon is independent of types of mediator and electrolyte. The acceleration originates from the overpotentials required to activate fast Li+/e− extraction and the following chemical step at specific abundant surface facets. Efficient redox catalysis at insulating solids therefore requires careful consideration of the surface conditions of the storage materials and electrolyte-dependent redox potentials, which may be tuned by salt concentrations or solvents.
Keywords: Process Chemistry and Technology; Biochemistry; Bioengineering; Catalysis

Microglia control glutamatergic synapses in the adult mouse hippocampus - Basilico, Bernadette; Ferrucci, Laura; Ratano, Patrizia; Golia, Maria T.; Grimaldi, Alfonso; Rosito, Maria; Ferretti, Valentina; Reverte, Ingrid; Sanchini, Caterina; Marrone, Maria C.; Giubettini, Maria; De Turris, Valeria; et al. (Glia)
Microglia cells are active players in regulating synaptic development and plasticity in the brain. However, how they influence the normal functioning of synapses is largely unknown. In this study, we characterized the effects of pharmacological microglia depletion, achieved by administration of PLX5622, on hippocampal CA3-CA1 synapses of adult wild type mice. Following microglial depletion, we observed a reduction of spontaneous and evoked glutamatergic activity associated with a decrease of dendritic spine density. We also observed the appearance of immature synaptic features and higher levels of plasticity. Microglia depleted mice showed a deficit in the acquisition of the Novel Object Recognition task. These events were accompanied by hippocampal astrogliosis, although in the absence ofneuroinflammatory condition. PLX-induced synaptic changes were absent in Cx3cr1−/− mice, highlighting the role of CX3CL1/CX3CR1 axis in microglia control of synaptic functioning. Remarkably, microglia repopulation after PLX5622 withdrawal was associated with the recovery of hippocampal synapses and learning functions. Altogether, these data demonstrate that microglia contribute to normal synaptic functioning in the adult brain and that their removal induces reversible changes in organization and activity of glutamatergic synapses.
Keywords: Cellular and Molecular Neuroscience; Neurology

Effects of streaky structures on the instability of supersonic boundary layers - Liu, Jianxin; Marensi, Elena; Wu, Xuesong (IUTAM Laminar-Turbulent Transition)
Streaky structures in the boundary layers are often generated by surface roughness elements and/or free-stream turbulence, and are known to have significant effects on boundary-layer instability. In this paper, we investigate the impact of two forms of streaks on the instability of supersonic boundary layers. The first concerns the streaks generated by an array of spanwise periodic and streamwise elongated surface roughness elements, and our interest is how these streaks influence the lower-branch viscous first modes, whose characteristic wavelength and frequency are on the classical triple-deck scales. By adapting the triple-deck theory in the incompressible regime to the supersonic one, we first derived a simplified system which allows for efficient calculation of the streaks. The asymptotic analysis simplifies a bi-global eigenvalue problem to a one-dimensional problem in the spanwise direction, showing that the instability is controlled at leading order solely by the spanwise-dependent wall shear. In the fundamental configuration, the streaks stabilize first modes at low frequencies but destabilize the high-frequency ones. In the subharmonic configuration, the streaks generally destabilize the first mode across the entire frequency band. Importantly, the spanwise even modes are of radiating nature, i.e. they emit acoustic waves spontaneously to the far field. Streaks of the second form are generated by low-frequency vortical disturbances representing free-stream turbulence. They alter the flow in the entire layer and their effects on instability are investigated by solving the inviscid bi-global eigenvalue problem. Different from the incompressible case, a multitude of compressible instability modes exists, of which the dominant mode is an inviscid instability associated with the spanwise shear. In addition, there exists a separate branch of instability modes that have smaller growth rates but are spontaneously radiating.

Alpha rhythm induces attenuation-amplification dynamics in neural activity cascades - Lombardi, Fabrizio; Herrmann, Hans J.; Parrino, Liborio; Plenz, Dietmar; Scarpetta, Silvia; Vaudano, Anna Elisabetta; de Arcangelis, Lucilla; Shriki, Oren (bioRxiv)
Rhythmical cortical activity has long been recognized as a pillar in the architecture of brain functions. Yet, the dynamic organization of its underlying neuronal population activity remains elusive. Here we uncover a unique organizational principle regulating collective neural dynamics associated with the alpha rhythm in the awake resting-state. We demonstrate that cascades of neural activity obey attenuation-amplification dynamics (AAD), with a transition from the attenuation regime—within alpha cycles—to the amplification regime—across a few alpha cycles—that correlates with the characteristic frequency of the alpha rhythm. We find that this short-term AAD is part of a large-scale, size-dependent temporal structure of neural cascades that obeys the Omori law: Following large cascades, smaller cascades occur at a rate that decays as a power-law of the time elapsed from such events—a long-term AAD regulating brain activity over the timescale of seconds. We show that such an organization corresponds to the "waxing and waning" of the alpha rhythm. Importantly, we observe that short- and long-term AAD are unique to the awake resting-state, being absent during NREM sleep. These results provide a quantitative, dynamical description of the so-far-qualitative notion of the "waxing and waning" phenomenon, and suggest the AAD as a key principle governing resting-state dynamics across timescales.

Cell surface fluctuations regulate early embryonic lineage sorting - Yanagida, Ayaka; Corujo-Simon, Elena; Revell, Christopher K.; Sahu, Preeti; Stirparo, Giuliano G.; Aspalter, Irene M.; Winkel, Alex K.; Peters, Ruby; De Belly, Henry; Cassani, Davide A.D.; Achouri, Sarra; Blumenfeld, Raphael; et al. (Cell)
In development, lineage segregation is coordinated in time and space. An important example is the mammalian inner cell mass, in which the primitive endoderm (PrE, founder of the yolk sac) physically segregates from the epiblast (EPI, founder of the fetus). While the molecular requirements have been well studied, the physical mechanisms determining spatial segregation between EPI and PrE remain elusive. Here, we investigate the mechanical basis of EPI and PrE sorting. We find that rather than the differences in static cell surface mechanical parameters as in classical sorting models, it is the differences in surface fluctuations that robustly ensure physical lineage sorting. These differential surface fluctuations systematically correlate with differential cellular fluidity, which we propose together constitute a non-equilibrium sorting mechanism for EPI and PrE lineages. By combining experiments and modeling, we identify cell surface dynamics as a key factor orchestrating the correct spatial segregation of the founder embryonic lineages.